Environmental impact of phosphogypsum stockpile in remediated Schistos waste site (Piraeus, Greece) using a combination of $γ$-ray spectrometry with geographic information systems - Papageorgiou, F; Godelitsas, A.; Mertzimekis, T. J.; Xanthos, S; Voulgaris, N.; Katsantonis, G (Environmental Monitoring and Assessment, 2016)
From 1979 to 1989, ten million tons of phosphogypsum, a waste by-product of the Greek phosphate fertilizer industry, was disposed into an abandoned limestone quarry in Schistos former waste site, Piraeus (Greece). The quarry has been recently closed and remediated using geomembranes and thick soil cover with vegetation. A part of the deposited phosphogypsum has been exposed due to intense rainfall episodes leading to concerns about how could potentially released radioactivity affect the surrounding environment. This study seeks to assess the environmental impact of the phosphogypsum deposited in the Schistos quarry, using laboratory-based $γ$-ray spectrometry measurements and geographical information systems. Radioactivity concentrations were mapped onto spatial-data to yield a spatial-distribution of radioactivity in the area. The data indicate elevated 226Ra concentrations in a specific area on the steep south-eastern cliff of the remediated waste site that comprises uncovered phosphogypsum and is known to be affected by local weather conditions. 226Ra concentrations range from 162 to 629 Bq/kg, with an average activity being on the low side, compared to the global averages for phosphogypsum. Nevertheless, the low environmental risk may be minimized by remediating this area with geomembranes and thick soil cover with vegetation, a technique, which has worked successfully over the remainder of the remediated quarry.